Apakah Kepuasan Pelanggan Air Mineral Aqua dipengaruhi oleh Harga dan Kualitas? - Meliyanti, Putu Indah; Susila, Gede Putu Agus Jana (Universitas Pendidikan Ganesha, 2021)
This study goal is to have a look at the impact of rate and product first-rate simultaneously and partially on patron satisfaction. The studies layout used became quantitative causal. The subjects of this studies are customers who buy Aqua mineral water at Rama Mart and the objects of research are charge, product first-rate, and patron pride. The sampling approach used became purposive sampling with a total of a hundred and twenty respondents. information collection changed into achieved by distributing questionnaires, then analyzed via a couple of linear regression evaluation. The results showed that (1) fee and Product high-quality had a tremendous and giant effect on purchaser pride of Aqua mineral water at Rama Mart with a contribution of 60.5% influence, (2) price had a high-quality and giant impact on Aqua consumer satisfaction. mineral water at Rama Mart. with an influence contribution of 29.five%, (3) Product nice has a high-quality and sizable impact on client delight of Aqua mineral water at Rama Mart with a power contribution of 23.5%.